Rasgos sociolectales en los estudiantes del 5°año “A”- secundaria- de la I.E. Liceo Trujillo-2019 - Palacios Briceño, Rolando Boanergues (2021)
Sociolectal features were identified and described in the 5th year “A” students of the I.E. Liceo Trujillo-2019 with the purpose of strengthening the culture peruvian and apply the linguistic knowledge. In the materials and methods, the research has been done looking for information about the sociolectal features, in addition, the population was all the students of the Secondary level of the Liceo Trujillo school, whose sample consists on the students of the 5th year "A" of the I.E. In addition, the technique used to collect the linguistic corpus wasthe recording of interviews using a survey. Then, it has been proceeded to the description and explanation in the five grammatical dimensions ofthe linguistic corpus. The results were that phonetic and phonological shortenings were made in the following words: oy!, oe !, pe !, cap,seten, mean, lamen, mu bien, ñeras, ta, pa llá; Also, there is yeísmo in “¡oe!”, “pa llá”,since there are shortened words, so morphologically and syntactically morphemes and grammatical categories have been omitted, as well, syntactically it has been used many pet words, for example , "Hey, hey, hey, well, um." Lexicologically and semantically the following words have been used: "blooper", "net", "roche", "breast", "pere" and "sucked". Asthere are manypet words, therefore, there is lexical poverty and syntactic disorder. Sincethere is yeísmo, then, the Castilian riparian is possessed. Since there are shortenings in the pronunciation and writing of the words, as well as, colloquial words are used, even slangs are used, the students, therefore, they have the basilect.